Belief and adherence to COVID 19-lockdown restrictions in patients with asthma versus other chronic diseases: results from a cross-sectional survey nested in the ComPaRe e-cohort, in France. (3rd August 2022) - Taillé, Camille; Roche, Nicolas; Tesson, Florian; Tardivon, Coralie; Tran, Viet-Thi; Couffignal, Camille
Abstract: Background: Asthma patients are under-represented among patients with COVID-19. Their behavior during lockdown and associated restrictions is unknown, as well as whether it was influenced by coexistent cardiovascular conditions. Methods: We conducted a cross-sectional survey in May 2020, in France, nested in ComPaRe, an e-cohort of adults with chronic diseases. A self-administered questionnaire was mailed to 10, 859 people; 3701 fully completed questionnaires. The prevalence of self-reported asthma was 7%. Patients were classified in 4 categories: asthma with ( n = 106) or without ( n = 149) cardiovascular disease and other diseases with ( n = 1186) or without ( n = 2260) cardiovascular disease. Result: Adherence to movement restrictions during the lockdown was very strong: 89% of participants reported a frequency of outings of "less than once per week" and "once or twice per week" for errands and no family-related outings during the lockdown. This proportion and frequency of outings were similar whatever the chronic disease ( p = 0.122). Most patients (96%) reported a high feeling of security during the lockdown, but 95% felt anxious or depressed, with no difference by disease. As compared with patients with controlled asthma, those with uncontrolled asthma more frequently reported complaints related to deteriorated medical follow-up, waived care, anxiety or depression. Conclusions: Behaviors during the lockdown in France among the asthma population did not differ from patients with other chronic diseases in this cohort, which strengthens hypotheses for specific disease-related susceptibility to explain the low representation of asthmatics among COVID-19 cases. Special attention should be paid to the subgroup of patients with uncontrolled asthma during lockdowns.